APRIL 17 BCIA BOARD MEETING - HAMILTON J (Tufts Archival Research Center, 2007)
Missing Attachments; Marginalia; Missing Page(s); Memo to Kay Thomas and Karen Fernicola from Joanna Hamilton summarizing a Business Council on Indoor Air (BCIA) meeting. Focuses on positioning BCIA favorably on indoor air quality legislation. Discusses letter from John Dingell and discussions with BOMA.